ANALISIS SISTEM AKUNTANSI PENGGAJIAN DAN PENGUPAHAN PADA PT. KARYA MITRA TEHNIK - Yuniar Nur Fadillah; Amin Sadiqin (LP2M Universitas Bina Bangsa, 2022)
The company is an important compenent is supporting management activities. The most important part is, the payroll and wage accounting system are very useful for companies, which can help to make decisions and achieve the implementation of salaries and wages for employees. The goal is to get the results of the implementation of the salary and wage process. In this study the author uses a qualitative descriptive method, which aims to read and analyze the performance of the accounting system at PT. Karya Mitra Tehnik. The results of this analysis show the salary and wage accounting system at PT. Karya Mitra Tehnik, which is still not support, and lack of supervision over employee attendance lists, this shows the weakness that occurs at PT.Karya Mitra Tehnik company on the payroll and wage accounting system